Predictors of Aggression Among Sample-Specific Young Adult Offenders: Continuation of Violent Behavior Within South African Correctional Centers - Jordaan, Jacques (International criminal justice review, 2022)
Offenders in South Africa face dehumanizing conditions in overcrowded correctional centers known for constant violence and corruption. These offenders need to cope and adjust to life within a correctional center. However, the majority of young adult male offenders use aggression to adjust to the correctional environment. It is, therefore, essential to identify which predictor variables predict aggression the best among incarcerated young adult male offenders. This study focused on 243 young adult male maximum-security offenders sampled through convenience sampling. Hierarchical multiple regression analyses were conducted to investigate which variable(s) or set(s) of variables explain a significant percentage of the variance of aggression. The results indicated that problem-solving, seeking social support, and avoidance, as a set of predictors, significantly predicted physical aggression, anger, and hostility. These findings seem to suggest that to decrease physical aggression, anger, and hostility among young adult offenders, it would be advisable to implement interventions that would (i) increase their problem-solving skills, (ii) improve their social support, and (iii) teach them to refrain from making use of avoidance as a coping strategy.